2021
DOI: 10.23887/jisd.v5i4.37885
|View full text |Cite
|
Sign up to set email alerts
|

The Principal's Role as Manager and Teacher Pedagogic Competence in Online Learning

Abstract: The Covid-19 pandemic requires people to learn online, one of which is at the elementary school level. Principals must be able to play a role as managers in managing learning during the Covid-19 Pandemic. This study aims to analyze the role of the principal as a manager and the pedagogical competence of teachers in online learning during the Covid-19 period. This type of research is descriptive quantitative research, namely by interpreting the data obtained from the field. Data collection was carried out on 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Furthermore, teachers also encountered difficulties in creating authentic assessments. This situation aligns with the conclusions of Ngaziah et al, (2021), who emphasized that teachers exhibited unsatisfactory pedagogical competence in the field of online learning, particularly in the areas of conducting learning outcome assessments and evaluating instructional materials. Kurnia et al, (2021) discovered various challenges encountered by primary school teachers in developing assessment tools are due to difficulties in (1) aligning basic competencies, indicators, and materials, (2) matching questions with basic competencies, indicators, and materials, (3) creating multiple-choice questions, essay questions, true-false questions, matching questions, and fill-in-the-blank questions, and (4) designing attitude assessments and skill assessments.…”
Section: Distinguish Between Uppercase and Lowercase Letterssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, teachers also encountered difficulties in creating authentic assessments. This situation aligns with the conclusions of Ngaziah et al, (2021), who emphasized that teachers exhibited unsatisfactory pedagogical competence in the field of online learning, particularly in the areas of conducting learning outcome assessments and evaluating instructional materials. Kurnia et al, (2021) discovered various challenges encountered by primary school teachers in developing assessment tools are due to difficulties in (1) aligning basic competencies, indicators, and materials, (2) matching questions with basic competencies, indicators, and materials, (3) creating multiple-choice questions, essay questions, true-false questions, matching questions, and fill-in-the-blank questions, and (4) designing attitude assessments and skill assessments.…”
Section: Distinguish Between Uppercase and Lowercase Letterssupporting
confidence: 86%
“…These findings align with the research findings of Nurtanto et al, (2021), who discovered that traditional teaching practices were still dominated by teacher-centered lecture-based approaches, with well-designed lesson plans rarely being implemented. Furthermore, Ngaziah et al, (2021) also indicated that teachers' pedagogical competencies still needed improvement in the context of learning, including the design of teaching methods and learning models.…”
Section: Teachers' Resistance To Changes In Learning Implementationmentioning
confidence: 99%
“…Principals need to make decisions so that the quality of education is maintained (Annisya & Ramadan, 2021;Arifa & Prayitno, 2019;Marmoah & Poerwanti, Suharno, 2022;Mayer, 2022). Principals need to carry out functions to achieve a goal (Ngaziah et al, 2021;Riani & Ain, 2022). Recruitment of honorary teachers is a decision taken by the school principal.…”
Section: Initial Situation When Working As An Honorary Teachermentioning
confidence: 99%